2021
DOI: 10.3390/foods10112688
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharides and Saponins Alleviate Liver Injury and Regulate Gut Microbiota in Alcohol Liver Disease Mice

Abstract: Astragalus, a medical and edible plant in China, shows several bioactive properties. However, the role of astragalus in attenuating alcoholic liver disease (ALD) is less clear. The objective of this project is to investigate the improving effect of astragalus saponins (AS) and astragalus polysaccharides (AP), which are the two primary constituents in astragalus on hepatic injury induced by alcohol, and the potential mechanisms of action. Different doses of AS (50 and 100 mg/kg bw) and AP (300 and 600 mg/kg bw)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…It is known that significant abnormalities in the intestine and an increase in serum IL‐1β levels are induced by regular consumption of alcohol. Furthermore, numerous studies have shown that the LPS‐TLR4/NF‐κB signaling pathway is closely associated with biological inflammation (Ju & Tacke, 2016; Tang et al, 2021; Xiao et al, 2020; Zhao et al, 2021; Zhou et al, 2021). The results showed that the liver LBP, TLR4, NF‐κB, and TGF‐β mRNA levels of the model group were higher than those in the control group (Figure 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that significant abnormalities in the intestine and an increase in serum IL‐1β levels are induced by regular consumption of alcohol. Furthermore, numerous studies have shown that the LPS‐TLR4/NF‐κB signaling pathway is closely associated with biological inflammation (Ju & Tacke, 2016; Tang et al, 2021; Xiao et al, 2020; Zhao et al, 2021; Zhou et al, 2021). The results showed that the liver LBP, TLR4, NF‐κB, and TGF‐β mRNA levels of the model group were higher than those in the control group (Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kupffer cells can activate hepatic stellate cells (HSCs) by producing the profibrotic cytokine TGF‐β (Ju & Tacke, 2016). There are several reports that endotoxin‐TLR4 NF‐κB pathway‐mediated inflammation may be one of its mechanisms of action to ameliorate alcoholic liver injury (Ju & Tacke, 2016; Tang et al, 2021; Xiao et al, 2020; Zhao et al, 2021; Zhou et al, 2021). Consistent with previous findings, we have shown that the liver LBP (LPS binding protein, receptor for LPS), TLR4, NF‐κB, and TGF‐β mRNA levels of the model group were higher than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…When liver dysfunction or hepatocytes are damaged, ALT and AST activities will increase significantly ( Xu et al, 2021 ). In stressed pigeons, Astragalus membranaceus and Ligustrum lucidum administration decreased blood levels of ALT, demonstrating their significance in reducing the detrimental effects of heat stress ( Lin et al, 2007 ; Abdelli et al, 2021 ; Zhou et al, 2021a ). The results of this test are similar to those of previous studies.…”
Section: Discussionmentioning
confidence: 97%
“… 2008 ; Zhou et al. 2021 ). In this study, the elevated levels of MDA, TC and TG was observed in iron overloaded mice.…”
Section: Discussionmentioning
confidence: 99%